Предмет: Алгебра, автор: SofyaCherry

Найдите значение выражения

Приложения:

Ответы

Автор ответа: Удачник66
3
 \frac{ \sqrt{47+12 \sqrt{11} } }{ \sqrt{6+ \sqrt{11} } } *\sqrt{6- \sqrt{11} }= \frac{ \sqrt{(47+12 \sqrt{11} )(6- \sqrt{11} )} }{ \sqrt{(6+ \sqrt{11} )(6- \sqrt{11} )} } * \sqrt{6- \sqrt{11} }=
=\frac{ \sqrt{282+72 \sqrt{11}-47 \sqrt{11}-12*11} }{ \sqrt{36-11} } * \sqrt{6- \sqrt{11} }= \frac{ \sqrt{150+25 \sqrt{11} } }{ \sqrt{25} } * \sqrt{6- \sqrt{11} }=
=\frac{ \sqrt{25*(6+\sqrt{11}) } }{ \sqrt{25} } * \sqrt{6- \sqrt{11} }=\sqrt{6+ \sqrt{11} }*\sqrt{6- \sqrt{11} }= \sqrt{36-11}=5
Похожие вопросы